Combining shell and GBT-based finite elements: Linear and bifurcation analysis. (July 2020) - Manta, David; Gonçalves, Rodrigo; Camotim, Dinar
Abstract: This paper proposes a general and efficient approach to model thin-walled members with complex geometries and/or connected through joints, by combining shell and standard GBT-based (beam) finite elements. It is shown that this approach is (i) very versatile, in the sense that complex geometries can be modelled quite easily, and (ii) computationally efficient, since the shell model substructures are condensed out of the global equilibrium equations. To show the capabilities of the proposed approach, several illustrative examples are presented and discussed, concerning the behaviour of (i) members with tapered segments, (ii) members with holes and (iii) complex beam-column assemblies. For validation purposes, full shell finite element model solutions are provided, showing that an excellent match is obtained. This paper deals exclusively with the linear (first-order) and bifurcation (linear stability) analysis cases, but the proposed approach will be extended to other analysis types. Highlights: GBT and standard shell elements are combined. Complex geometries, holes and joints can be easily modelled. The GBT elements only require a small number of deformation modes. The shell macro-element DOFs are condensed out of the equilibrium equations. Linear and bifurcation analyses are carried out.